Cervical Myelopathy Due to a Hypoplastic Atlas - Duz, Bulent; Kaplan, Metin; Tehli, Ozkan; Kahraman, Serdar (Lippincott Williams & Wilkins, 2008)
Congenital hypoplasia of the atlas is a rare cause of cervical myelopathy. We report a case of a 30-year-old man with cervical myelopathy caused by spinal stenosis at the level of the atlas associated with a hypoplastic but complete posterior arch of Cl. Repetitive and persistent hyperextension causes micro-traumas at the level of spinal stenosis in the spinal cord. Hypoplasia of the atlas may result in serious neurologic manifestations and complications in time. In our case, the spinal canal diameter was calculated to be 11 mm at the level of the atlas on computerized tomography imaging. However, this diameter was 8 mm on magnetic resonance imaging owing to the thickened atlanto-occipital membrane. We suggest that the spinal canal diameter should be measured by magnetic resonance imaging,. Treatment of developmental cervical stenosis is surgical removal of the thickened posterior arc of the atlas and surrounding degenerative ligaments in symptomatic cases. The symptoms related to myelopathy may improve after surgery.
Keywords: cervical stenosis; hypoplasia of the atlas; cervical myelopathy